2018
DOI: 10.1038/s41418-018-0208-2
|View full text |Cite
|
Sign up to set email alerts
|

EZH2-DNMT1-mediated epigenetic silencing of miR-142-3p promotes metastasis through targeting ZEB2 in nasopharyngeal carcinoma

Abstract: Human nasopharyngeal carcinoma (NPC) has the highest metastatic rate in head and neck. However, the mechanisms underlying NPC metastasis remain unclear. Here using propensity-score-matched miRNA microarray analysis, miR-142-3p is identified to be the most correlated with distant-metastasis-free survival and downregulated in paraffin-embedded NPC with distant metastasis, which is validated in both internal cohort and external GEO dataset from Canada. miR-142 locus hypermethylation was observed and found to be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 57 publications
3
36
0
Order By: Relevance
“…Among the 15 miRNAs in the ceRNAs, hsa-miR-142-3p was demonstrated to be down-regulated in NPC, and a high level of hsa-miR-142-3p indicated favorable prognosis, which was consistent with the previous studies [39,40]. Li Y et al revealed that miR-142-3p was epigenetically silenced by EZH2-recruited DNMT1 and suppress NPC cell metastasis and EMT through targeting ZEB2 [41]. However, Qi et al reported that miR-142-3p inhibits the expression of SOCS6 and promotes cell proliferation in NPC [42].…”
Section: Discussionsupporting
confidence: 85%
“…Among the 15 miRNAs in the ceRNAs, hsa-miR-142-3p was demonstrated to be down-regulated in NPC, and a high level of hsa-miR-142-3p indicated favorable prognosis, which was consistent with the previous studies [39,40]. Li Y et al revealed that miR-142-3p was epigenetically silenced by EZH2-recruited DNMT1 and suppress NPC cell metastasis and EMT through targeting ZEB2 [41]. However, Qi et al reported that miR-142-3p inhibits the expression of SOCS6 and promotes cell proliferation in NPC [42].…”
Section: Discussionsupporting
confidence: 85%
“…Among the 15 miRNAs in the ceRNAs, hsa-miR-142-3p was demonstrated to be down-regulated in NPC, and a high level of hsa-miR-142-3p indicated favorable prognosis, which was consistent with the previous studies [16,42]. Li Y et al revealed that miR-142-3p was epigenetically silenced by EZH2-recruited DNMT1 and suppress NPC cell metastasis and EMT through targeting ZEB2 [43]. However, Qi et al…”
Section: Discussionsupporting
confidence: 75%
“…10,12 The dysregulated miRNAs play an important role in NPC tumorigenesis and progression by promoting NPC cell proliferation, invasion, and angiogenesis. [13][14][15][16] It has been found that miR-125b is upregulated in NPC, and it can promote NPC cell proliferation and inhibit cell apoptosis by targeting A20 and activating the NF-kB signaling pathway. 13 miR-506 can inhibit NPC tumor growth and metastasis through inactivating the Wnt/β-catenin signaling pathway by targeting LHX2.…”
Section: Discussionmentioning
confidence: 99%
“…14 EZH2-DNMT1mediated epigenetic silencing of miR-142-3p promotes NPC cell invasion and metastasis by targeting ZEB2. 15 miR-23a can promote NPC cell growth, migration, and angiogenesis by targeting TSGA10. 16 Here, in our present study, we found that miR-100 was obviously decreased in NPC tissue samples by analyzing three publicly available microarray data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation